Sweet Syndrome due to Myelodysplastic Syndrome: Possible Therapeutic Role of Intravenous Immunoglobulin in Addition to Standard Treatment - Harry H. S. Gill; Anskar Y. H. Leung; N. J. Trendell-Smith; C. K. Yeung; Raymond Liang (Advances in Hematology)
We report an 82-year-old lady who developed sudden onset nodular and erythematous lesions and neutrophilia following an episode of urinary tract infection. Skin biopsy confirmed the diagnosis of Sweet syndrome. Response to the use of prednisolone alone was not satisfactory. The skin lesions however showed a sustained response to the regular use of intravenous immunoglobulin (IVIG) and prednisolone was slowly weaned off. Our case highlights the possible therapeutic role of IVIG in managing this condition.